Repair gene O 6 ‐methylguanine‐DNA methyltransferase is controlled by SP1 and up‐regulated by glucocorticoids, but not by temozolomide and radiation - Aasland, Dorthe; Reich, Thomas R.; Tomicic, Maja T.; Switzeny, Olivier J.; Kaina, Bernd; Christmann, Markus (Journal of neurochemistry, 2018)
Therapy of malignant glioma relies on treatment with the O -methylating agent temozolomide (TMZ) concomitant with ionizing radiation followed by adjuvant TMZ. For the treatment of recurrences, DNA chloroethylating drugs are also used. The main killing lesion induced by these drugs is O -alkylguanine. Since this damage is repaired by O -methylguanine-DNA methyltransferase (MGMT), the repair enzyme represents a most important factor of drug resistance, limiting the therapy of malignant high-grade gliomas. Although MGMT has been shown to be transcriptionally up-regulated in rodents following genotoxic stress, it is still unclear whether human MGMT is subject to up-regulation. Here, we addressed the question whether MGMT in glioma cells is enhanced following alkylating drugs or ionizing radiation, using promoter assays. We also checked the response of glioma cell lines to dexamethasone. In a series of experiments, we found no evidence that the human MGMT promoter is significantly up-regulated following treatment with TMZ, the chloroethylating agent nimustine or radiation. It was activated, however, by dexamethasone. Using deletion constructs, we further show that the basal level of MGMT is mainly determined by the transcription factor SP1. The high amount of SP1 sites in the MGMT promoter likely prevents transcriptional up-regulation following genotoxic stress by neutralizing inducible signals. The regulation of MGMT by miRNAs plays only a minor role, as shown by DICER knockdown experiments. Since high dose dexamethasone concomitant with temozolomide is frequently used in glioblastoma therapy, induction of the MGMT gene through glucocorticoids in MGMT promoter unmethylated cases might cause further elevation of drug resistance, while radiation and alkylating drugs seem not to induce MGMT at transcriptional level.